Investigating the effect of organizational knowledge sharing on innovation performance with the mediating role of innovation capability and moderating scale of networking and communication power (case study of small and medium-sized companies in Iraq) - Amir Adnan Hasoon Alkhafaji; Omid Behboodi; Mohsen Moradi (مدیریت راهبردی دانش سازمانی, 2023)
Innovation is an important indicator for organizations because it creates value and sustainable competitive advantage in the current complex and changing environment. More innovative organizations are more successful than other organizations in responding to changing environments and creating and expanding new capabilities and achieving better performance. Therefore, the purpose of this research was to investigate the effect of organizational knowledge sharing on the innovation performance of Iraqi small and medium enterprises with the mediating role of innovation capability and moderating Connection strength and networking scale. The statistical population of this research is all managers and vice presidents of small and medium companies in Iraq, whose number is unknown; According to Klein's thumb method (5 to 10 times the number of items), the number of members of 170 people was selected non-randomly. The research tool was Dongling et al.'s (2022) questionnaire, which was used to test the validity of content validity and experts' approval, and for construct validity, construct validity, convergent and divergent validity were used. The reliability of the questionnaire was done with Cronbach's alpha and composite reliability (more than 0.7). Data analysis was done by structural equation method with PLS software. The results showed that the effect of organizational knowledge sharing on innovation performance with the mediation of innovation capability was significant (t=2.559). In addition, the moderating role of networking scale (t=2.671) and Connection strength (t=3.651) in the effect of organizational knowledge sharing on innovation ability has been reported.